Precificação da colheita de sementes nativas em redes comunitárias - Perussi, Gabriel (2023)
The large number of areas to be restored in Brazil, whether due to national legislation or international agreements, generates a great demand for native seeds to meet restoration projects. Even with the performance of community seed networks throughout the country, the seed supply market faces several difficulties, such as the discrepancy in seed sales prices and the disorganized market structure. To better understand how this market works, it is necessary to understand which factors can influence the cost of production of native seed. For this, the present work proposed to evaluate which variables from different contexts influence the cost of production. Data were collected in the field, but also in bibliographic searches, and semi-structured interviews were carried out in order to explore several variables that permeate the work of seed harvesting. Data were analyzed by Spearman correlations and comparison of means with standard error graphs and Mann-Whitney tests. However, of the listed variables, none showed a statistically significant value that, with the variable alone, it was possible to predict some behavior of the final production cost of the seed in R$/kg. This indicates that seed cost relationships may be more complex than expected in this work, and a multivariate statistical approach may be necessary. However, it was still possible to document important information about the harvesting process that had not previously been recorded in specialized bibliography.